Mathematical Modeling for the Development of a Multilevel ;Electronic Physician Assistant and Simplified Assignment of Corrective Therapy to Immunocompromised Patients (Global Journal of Medical Research, 2021)
The development of a multilevel "electronic doctor's assistant" for identifying immunologically compromised persons and the choice of optimal differentiated immunotherapy for pyo-inflammatory and other diseases is outlined.
Keywords: mathematical modeling; pre-laboratory analysis; immunopathological syndrome; immune correction